Pengaruh Atribut Brand Ambassador Syahrini Terhadap Keputusan Pembelian Tora Bika Kopi Susu (studi kasus pada santri pesantren Mahasiswa Al Hikam malang) - Muhamad Yusuf Fikri Habibi; N. Rachma; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to determine the effect and analyze the effect of visibility, credibility, attraction, power and purchasing decisions simultaneously and partially on the purchase decision of Tora Bika Kopi Susu. The population in this study was in the santri pesantren of Al Hikam Malang students. The sample used in this study was 93 respondents. The sampling technique to determine the sample to be used in this study uses non probability sampling, namely purposive sampling. Purposive sampling is a limiting method of sampling a person's special characteristics which provides information that is more focused and in accordance with what the researcher wants. Analysis was carried out using questionnaires. The results of this study indicate Visibility / X1 (006), Credibility / X2 (001), Attraction / X3 (000), Power / X4 (000) show partially the results (t test) have a significant effect on purchasing decisions. While simultaneous results (f test) on the table obtained F in the count of 36,653 and a probability of 0,000. Because sig F count <5% (0,000 <0,05), shows simultaneously significant effect on purchasing decisions. Keywords: Visibility, Credibility, Attraction, Power and purchasing decisions